2016
DOI: 10.4172/2167-7182.1000267
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Unmet Needs among African-American Dementia Care Providers

Abstract: Racial and ethnic minorities currently comprise 20% of the U.S. population; in 2050, this figure is expected to rise to 42%. As a result, Alzheimer’s disease (AD), the 5th leading cause of death for people aged 65 and older, is likely to increase in these groups. Most dementia caregiving for these populations comes from family and friends, especially among families with lower socioeconomic status. A convenience sample of 30 African-American dementia caregivers was interviewed to determine unmet needs. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…These results corroborate previous studies that have tested the efficacy of psychoeducational interventions for ADRD caregivers. Previous research suggests that psychoeducational interventions in particular have been shown to positively affect ADRD caregiver stress (Mart ın-Carrasco et al, 2009), improve mental health (O'Rourke et al, 2010), and lessen caregivers' bother of memory related behavioral problems (Desin et al, 2016). Furthermore, study findings are consistent with previous research suggesting that home-based interventions may improve caregiver well-being (Gitlin, Winter, Dennis, Hodgson, & Hauck, 2010).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These results corroborate previous studies that have tested the efficacy of psychoeducational interventions for ADRD caregivers. Previous research suggests that psychoeducational interventions in particular have been shown to positively affect ADRD caregiver stress (Mart ın-Carrasco et al, 2009), improve mental health (O'Rourke et al, 2010), and lessen caregivers' bother of memory related behavioral problems (Desin et al, 2016). Furthermore, study findings are consistent with previous research suggesting that home-based interventions may improve caregiver well-being (Gitlin, Winter, Dennis, Hodgson, & Hauck, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…Finally, study results also showed that received social support of caregivers significantly increased after the SCP Plus. This is a key finding as many African American ADRD caregivers express a desire for family and social support (Desin et al, 2016) and wish for broader sharing of caregiving responsibility within families (Samson et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Educational programs could be targeted to caregivers, family members (Desin et al, 2016), and individuals in early disease stages, alike, and primarily focus on the clinical course of dementia and issues related to end-of-life care, including health care decision-making and treatment options. To date, evidence for the efficacy of interventions to increase participation in care planning among persons with dementia is limited (Bryant et al, 2018), although discussions related to goals of care may be associated with an increased acceptance of dementia diagnosis among health care proxies (Givens et al, 2018).…”
Section: Discussionmentioning
confidence: 99%